Analisis Aplikasi Pengolahan Zakat Online dan Pengelolaan Zakat Berbasis Jaringan Virtual - Abdul Hafiz (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2021)
Technological developments currently penetrate the world of worship, forthose who want to pay zakat it is even easier. A number of online applications,including online shopping, provide zakat payment features for muzakki.Looking at the data available at the National Amil Zakat Agency that thepotential for zakat in 2019, based on the IIPZ association and the outlook forIndonesian zakat, the potential for zakat is around Rp. 233.8 Trillion which isdivided into 5 Zakat objects. In 2016 and 2017, zakat income was only around6 trillion. The potential of zakat is very large in Indonesia, making all zakatpractitioners or zakat collection agencies have to find ways to maximize thepotential of zakat and be able to alleviate poverty in Indonesia. From anefficient zakat management effort, the manager as Amil zakat implements anonline application system for zakat both based on Android and Web, the aim isto facilitate and improve zakat services for the better, with this online zakatapplication it is expected to be able to absorb some of the existing zakatpotential and help make it easier for people to pay zakat because of the limiteddistance and time. The general purpose of this research is for the developmentand growth of zakat to increase with the collection of zakat through online. Inparticular, to make it easier for muzakki in distributing zakat. This researchuses qualitative research methods which are commonly referred to asnaturalistic research methods because the research is carried out in naturalconditions (natural settings), the research data sources are primary andsecondary. The results and research findings are that there is a growth in zakatfrom every year either from the growth of zakat in the online zakat system orin zakat income as a whole every year. Perkembangan teknologi saat ini merambah dunia ibadah, bagi mereka yangingin membayar zakat pun semakin dipermudah. Sejumlah aplikasi onlinetermasuk belanja online menyediakan fitur pembayaran zakat bagi muzakki.Potensi zakat yang sangatlah besar di Indonesia, membuat semua praktisi zakatataupun badan penghimun zakat harus mencari cara bagaimana agar potensizakat yang ada bisa maksimal dan mampu mengetaskan kemiskinan diIndonesia. Dari upaya pengelolaan zakat yang efisien Pengelola selaku Amilzakat menerapkan sistem aplikasi online untuk berzakat baik yang berbasisandroid dan Web, tujuannnya agar memudahkan dan meningkatkan pelayananzakat menjadi lebih baik, dengan adanya aplikasi zakat online ini diharapkanmampu menyerap sebagian potensi zakat yang ada serta membantumemudahkan masyarakat membayar zakat karena terbatas jarak danwaktu.Tujuan penelitian ini secara umum adalah agar perkembangan danpertumbuhan zakat semakin meningkat dengan adanya penghimpunan zakatmelalui online. Secara khusus agar memudahkan para muzakki dalammenyalurkan zakat. Penelitian ini menggunakan metode penelitian kualitatifyang biasa disebut dengan metode penelitian naturalistik karena penelitianyadilakukan pada kondisi yang alamiah (natural setting), sumber data penelitianyaitu primer dan sekunder. Hasil dan temuan penelitian adalah adanyapertumbuhan zakat dari setiap tahun baik dari pertumbuhan zakat di sistemzakat online ataupuun di pendapatan zakat secara kseluruhan setiap tahun.